Synthesis of the debates - Guibentif, P. (Knowing Justice in the Anthropocene, 2025)
Synthesis of the debates held in the sessions organized by RCSL at the V ISA Forum of Sociology, Knowing Justice of the Anthropocene, presented as an introduction to the concluding debate which closed the RCSL Sessions at the Forum, Rabat.